2013
DOI: 10.17221/57/2013-pse
|View full text |Cite
|
Sign up to set email alerts
|

Effects of tillage on soil physical properties and root growth of maize in loam and clay in central China

Abstract: Subsoil compaction can result in unfavourable soil physical conditions and hinder the root growth of maize. The effects of deep tillage and conventional tillage on soil physical properties and root growth of maize were studied during 2010-2011 at two sites (loam at Hebi and clay at Luohe) in central China. The results showed that soil penetration resistance, bulk density, water content and root length density were significantly affected by tillage, soil depth and year. Deep tillage had lower penetration resist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
21
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(35 citation statements)
references
References 18 publications
6
21
1
2
Order By: Relevance
“…According to these authors, the root length density of corn plants grown in soil under NT were 4.2; 1.8 and 1.8 cm root per soil cubic cm, respectively in the 0-0.05 m; 0.10-0.15 m; and 0.25-0.35 m layers. However, our results were higher than those observed to Foloni et al (2003) and Ji et al (2013).…”
Section: Development Of Corn Plantscontrasting
confidence: 86%
“…According to these authors, the root length density of corn plants grown in soil under NT were 4.2; 1.8 and 1.8 cm root per soil cubic cm, respectively in the 0-0.05 m; 0.10-0.15 m; and 0.25-0.35 m layers. However, our results were higher than those observed to Foloni et al (2003) and Ji et al (2013).…”
Section: Development Of Corn Plantscontrasting
confidence: 86%
“…While DD practice was the practice which caused the most soil compaction, C+D+RT+DSM and P+RT+DSM practices were the ones that caused the least soil compaction. Ji et al (2013) examined the effects of deep and traditional tillage on physical soil properties and the root development of corn in two different areas having clayey and silty texture during the years 2010-2011. They reported that soil penetration resistance, bulk density, water content, and root length density showed statistically significant differences in terms of tillage, soil depth, and years, whereas deep soil tillage decreased penetration resistance and bulk density values.…”
Section: Assessment Of Soil Quality Indicatorsmentioning
confidence: 99%
“…We expect, therefore, that our results are also valid for mechanical deep tillage, especially since our results are in agreement with [20], which reported lower bulk density with deep tillage treatments and higher bulk density with NT. Other studies [21] also reported that deep tillage resulted in lower bulk density and penetration resistance than conventional tillage. Similarly, [22] found that the application of deep tillage down to a 90 cm depth in soils with a fragipan resulted in a significant reduction in bulk density and penetration resistance.…”
Section: Effect Of Deep Tillage On Soil Erosion and Runoffmentioning
confidence: 86%